ARTERIAL STIFFNESS IN CHRONIC HEART FAILURE - O. M. Drapkina; V. A. Dadaeva (Klinicist)
Nearly half of patients with chronic heart failure (CHF) have a preserved left ventricular ejection fraction, known as diastolic heart failure. Echocardiography is the primary modality for evaluating left ventricular (LV) systolic and diastolic function in CHF patients. LV developedpressure (dP/dt) is a classical index of myocardial contractility. At the same time, pulse wave velocity, which has been used as a measure of arterial stiffness, can be used as an index of LV contractile function. The maximal dP/dt of the radial pulse appears to be a good and reproducible criterion of LV systolic performance with high potential as a diagnostic method.